Ruang publik, Media sosial, Demokrasi, dan Pendekatan kritis. - Wahyudi, R.Firdaus; Musliadi, Musliadi; Muhlis, Muhlis; Faridah, Faridah (LP2M Universitas Islam Ahmad Dahlan Sinjai, 2024)
The Public sphere as initiated by Habermas, was a possible domain for citizen to participate actively in discussing public issues. In democratically public sphere, participated citizen was protected by Law and be treated equally in his/her function and role in such public sphere. Public sphere was rationally discourse domain and free form intervention of the power and economy logic. The existence of social media had transformed of the public sphere, so that create possibility for every citizen involved actively and independently in the discourses of public issues. This research was qualitative research by use library research method that had relevancy to the topic of critical study of public sphere mediated by social media. This research described that social media with interactivity feature and create became producer and consumer of contents at once, enabling to the dissemination process or the ideas intercourse due to the public issues as idealized by democracy. However, social media had dark or negative side that could ruin such ideal public sphere, such as: media social tent to become fake or hoax dissemination arena and create polarization or fragmentation of group. The social media was based on exploitatively and unequally operation because the hegemony and surveillance of the giant corporate of media such as Facebook, Amazon, Microsoft and so on.